First Translation of Šejh Sadi’s Gulistan Into Serbo-Croatian - Trako, Salih (Prilozi za orijentalnu filologiju, 2017)
Under the title of “Zubde-i Gulistan” the text of the famous mystical-didactical wovk “Gulistan” by the great Persian classic Sejḫ Sa'dī with a parallel Turkish translation made by Ğa'far Ṭayyār b. Aḥmad Sālim was published in Istanbul at the end of the last century. Without changing the title, this printed work was copied and translated into Serbo-Croatian by Yūnus Remzī Stovro of Sarajevo in 1897. Stovro thus did as Ğa'far Ṭayyar did: he made a parallel translation. Namely, next to the existing text of Gulistan in the Persian original and its Turkish translation, Stovro made a Serbo-Croatian translation as well. This autograph of Stovro ~ which was discovered thanks to Dr. Muhamed Hadžijahić of Sarajevo and is now the property of the Academy of Arts and Sciences of Bosnia and Herzegovina - represents, in several respects, a valuable example of aljamiado literature from the area of Bosnia and Herzegovina where this literature - as is the case with the whole of the Balkan Peninsula - has not been explored enough yet. There are numerous pieces of evidence concerning its existence in the 17th, 18th, and the 19th centuries, when it was cherished. A good many preserved manuscripts of aljamiado literature are kept today in the collections of oriental manuscripts of some scholarly institutions in Sarajevo, Zagreb, Beograd, Skoplje, Priština, and some other smaller cultural centers in Yugoslavia. These documents doubtless represent very interesting literary material which deserves scholarly treatment and serious investigation. That which makes Stovro's autograph exceptionally valuable, and that is what this article is about, does not consist only in the fact that it has preserved the Sarajevo vernacular language from the end of the last century, a speech which can now be heard only among old Sarajevo citizens, nor in the claim that the work, to the best of our knowledge, represents the largest complete piece of writing in aljamiado literature on our soil, but in the fact that here was applied a special orthography whose inventor was Stovro himself and which is to be found nowhere else. Stovro invented his own principles of orthography and carried them out strictly throughout his work. This attempt to adapt consistently the Arabic alphabet to the writing of the Serbo-Croatian language and to translate completely a famous classic work of Persian literature into Serbo-Croatian is a reason important enough, not only -for orientalists but also for slavists who study aljamiado literature and the development of the Serbo-Croatian language in general, to devote their attention to this work.